2017
DOI: 10.1111/acem.13351
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Double Blind Trial of Needle‐free Injected Lidocaine Versus Topical Anesthesia for Infant Lumbar Puncture

Abstract: In a randomized controlled trial of two modalities for local anesthesia in infant LPs, J-Tip was not superior to TA cream as measured by pain control or physiologic changes. Infant LPs performed with J-Tip were twice as likely to be successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Comparative studies between J‐tip and other topical anesthetics have been performed. Infants undergoing lumbar punctures were given either a topical placebo cream plus J‐tip delivered lidocaine versus topical EMLA cream plus J‐tip delivered saline (placebo), and no significant pain difference was observed, suggesting EMLA may be equally effective 85 . Another study looking at pediatric venipuncture found EMLA actually outperformed J‐tip, but pain scores were overall low and neither intervention significantly decreased fear 86 .…”
Section: On the Horizonmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative studies between J‐tip and other topical anesthetics have been performed. Infants undergoing lumbar punctures were given either a topical placebo cream plus J‐tip delivered lidocaine versus topical EMLA cream plus J‐tip delivered saline (placebo), and no significant pain difference was observed, suggesting EMLA may be equally effective 85 . Another study looking at pediatric venipuncture found EMLA actually outperformed J‐tip, but pain scores were overall low and neither intervention significantly decreased fear 86 .…”
Section: On the Horizonmentioning
confidence: 99%
“…Infants undergoing lumbar punctures were given either a topical placebo cream plus J-tip delivered lidocaine versus topical EMLA cream plus J-tip delivered saline (placebo), and no significant pain difference was observed, suggesting EMLA may be equally effective. 85 Another study looking at pediatric venipuncture found EMLA actually outperformed J-tip, but pain scores were overall low and neither intervention significantly decreased fear. 86 At this V I D E O 3 This adolescent patient is undergoing planned multimodal treatment of an acne keloid on her superior chest.…”
Section: J-tipmentioning
confidence: 99%